Amphiphilic diblock copolymer-mediated structure control in nanoporous germanium-based thin films. Issue 4 (15th January 2019) - Hohn, Nuri; Hetzenecker, Andreas E.; Giebel, Michael A.; Geier, Sebastian; Bießmann, Lorenz; Körstgens, Volker; Saxena, Nitin; Schlipf, Johannes; Ohm, Wiebke; Deimel, Peter S.; Allegretti, Francesco; Barth, Johannes V.; et al.
Abstract : Porous Ge-based thin films processed from PS- b -PEO templated K4 Ge9 precursor. Abstract : Fabrication of porous, foam-like germanium-based (Ge-based) nanostructures is achieved with the use of the amphiphilic diblock copolymer polystyrene- b -polyethylene oxide as structure directing agent. Basic concepts of block copolymer assisted sol–gel synthesis are successfully realized based on the [Ge9 ] 4− Zintl clusters as a precursor for Ge-based thin films. Material/elemental composition and crystalline Ge-based phases are investigated via X-ray photoelectron spectroscopy and X-ray diffraction measurements, respectively. Poor-good solvent pair induced phase separation leads to pore sizes in the Ge-based films up to 40 nm, which can be tuned through a change of the molar mixing ratio between polymer template and precursor as proven by grazing incidence small angle X-ray scattering and scanning electron microscopy.